Atlas of gray matter volume differences across psychiatric conditions: a systematic review with a novel meta-analysis that considers co-occurring disorders : archival report - Fortea, Lydia; Ortuño, Maria; De Prisco, Michele; Oliva, Vincenzo; Albajes-Eizagirre, Anton; Fortea, Adriana; Madero, Santiago; Solanes, Aleix; Vilajosana, Enric; Yao, Yuanwei; Del Fabro, Lorenzo; Solé, Eduard; et al. (Biological psychiatry, 2025)
Background - Regional gray matter volume (GMV) differences between individuals with mental disorders and comparison participants may be confounded by co-occurring disorders. To disentangle disorder-specific GMV correlates, we conducted a large-scale multidisorder meta-analysis using a novel approach that explicitly models co-occurring disorders. - Methods - We systematically reviewed voxel-based morphometry studies indexed in PubMed and Scopus up to January 2023 that compared adults with major mental disorders (anorexia nervosa, schizophrenia spectrum, anxiety, bipolar, major depressive, obsessive-compulsive, and posttraumatic stress disorders plus attention-deficit/hyperactivity, autism spectrum, and borderline personality disorders) with comparison participants. Two authors independently extracted data and assessed quality using the Newcastle-Ottawa Scale. We derived GMV correlates for each disorder using: 1) a multidisorder meta-analysis that accounted for all co-occurring mental disorders simultaneously and 2) separate standard meta-analyses for each disorder in which co-occurring disorders were ignored. We assessed the alterations’ extent, intensity (effect size), and specificity (interdisorder correlations and transdiagnostic alterations) for both approaches. - Results - We included 433 studies (499 datasets) involving 19,718 patients and 16,441 comparison participants (51% female, ages 20-67 years). We provide GMV correlate maps for each disorder using both approaches. The novel approach, which accounted for co-occurring disorders, produced GMV correlates that were more focal and disorder specific (less correlated across disorders and fewer transdiagnostic abnormalities). - Conclusions - This work offers the most comprehensive atlas of GMV correlates across major mental disorders. Modeling co-occurring disorders yielded more specific correlates, supporting this approach’s validity. The atlas NIfTI maps are available online.
Online verfügbar: 2. November 2024, Artikelversion: 11. Juni 2025
Gesehen am 11.11.2025